Variation in the life-history traits of a Schilbid catfish, Clupisoma garua (Hamilton, 1822) in the coastal waters of southern Bangladesh - Siddik, M.; Chaklader, M.; Hanif, M.; Nahar, A.; Ilham; Cole, A.; Fotedar, Ravi (2017)
For the fi rst time, the present study reports the life-history traits, comprising length-frequency distribution (LFD), sex ratio (SR), length-weight relationships (LWRs), condition factors (CFs), and relative growth ( W R ), of Clupisoma garua in the coastal waters of Bangladesh. A total of 150 specimens ranging from 8.60 to 25.20 cm total length (TL) and 4.26 to 128.80 g body weight (BW) were collected using traditional fi shing gear from August 2013 to July 2014. The overall sex ratio of males to females in the study did not diff er signifi cantly from the expected value of 1:1 ( ? 2 =0.96, P <0.05) but there were signifi cant sex diff erences ( P <0.05) in the intercepts and slopes of graphs characterizing traits in Clupisoma garua . The calculated b values for the LWRs were 2.955, 2.893 and 2.927 for males, females and combined sexes, respectively, and there was negative allometric growth in all cases ( b <3). The condition factors ( K A , K F , K R ) and relative growth ( W R ) also did not diff er signifi cantly ( P <0.05) between the sexes. This study provides a useful tool for fi shery specialists to evaluate the relative condition of fi sh and to initiate early management strategies and regulations for the sustainable management of the remaining stocks of this species in the entire coastal region of southern Bangladesh.